Arrhythmogenicity of Anti-Ro/SSA Antibodies in Patients With Torsades de Pointes. (April 2016) - Lazzerini, Pietro Enea; Yue, Yuankun; Srivastava, Ujala; Fabris, Frank; Capecchi, Pier Leopoldo; Bertolozzi, Iacopo; Bacarelli, Maria Romana; Morozzi, Gabriella; Acampa, Maurizio; Natale, Mariarita; El-Sherif, Nabil; Galeazzi, Mauro; et al.
Abstract : Background—: In patients with autoimmune disease, anti-Ro/SSA antibodies (anti-Ro/SSA) are responsible for a novel autoimmune-associated long-QT syndrome by targeting the hERG potassium channel and inhibiting the related current ( I Kr ). Because anti-Ro/SSA are also present in a significant proportion of healthy subjects and may be associated with torsades de pointes (TdP) arrhythmia, we tested the hypothesis that anti-Ro/SSA may represent a silent risk factor in patients developing TdP. Methods and Results—: Twenty-five consecutive patients who experienced TdP were prospectively collected independent of ongoing therapies and concomitant diseases. Anti-Ro/SSA were detected by fluoroenzyme immunoassay, immuno–Western blotting, and line-blot immunoassay. Purified IgGs from anti-Ro/SSA-positive and anti-Ro/SSA-negative patients were tested on I Kr using HEK293 cells stably expressing the hERG channel. As expected, in TdP patients, many known corrected QT interval–prolonging risk factors were simultaneously present, including hypokalemia that was the most common (52%). Anti-Ro/SSA were present in 60% of the subjects, mostly the anti-Ro/SSA-52-kD subtype detected by immuno–Western blotting only. A history of autoimmune disease was found in only 2 of anti-Ro/SSA-positive patients. Experimental data demonstrated that purified anti-Ro/SSA-positive IgGs significantly inhibited I Kr and cross reacted with hERG-channel proteins. Moreover, anti-Ro/SSA-positive sera exhibited high reactivity with a peptide corresponding to the hERG-channel pore-forming region. Conclusions—: Anti-Ro/SSA may represent a clinically silent novel risk factor for TdP development via an autoimmune-mediated electrophysiological interference with the hERG channel. We propose that TdP patients may benefit from specific anti-Ro/SSA testing even in the absence of autoimmune diseases as immunomodulating therapies may be effective in shortening corrected QT interval and reducing TdP recurrence risk. Abstract : Supplemental Digital Content is available in the text.